Stations of awakening: musical subject-strategies in the unconscious levels of the video games Kingdom hearts: birth by Sleep (2011) & Persona 5 (2017) - Stevens, Joshua (Stellenbosch : Stellenbosch University, 2024)
Thesis (MMus)--Stellenbosch University, 2024.